Ecological perspectives on technological diversity at Kanjera South. Issue 158 (September 2021) - Reeves, Jonathan S.; Braun, David R.; Finestone, Emma M.; Plummer, Thomas W.
Abstract: The aspects of hominin behavior responsible for Oldowan stone tool variation are the focus of much debate. There is some consensus that this variation arises from a combination of ecological and cultural factors. The diversity of raw material types and technological strategies present at Kanjera South, Kenya, provide an opportunity to examine the interacting influences of ecology and culture on Oldowan stone tool variation. Here, we combine previous analyses of raw material properties, provenance, and technology with quantitative measures of core reduction intensity and tool utilization to examine the influence of both ecological and technocultural factors on stone tool variation at Kanjera South. The results of this analysis reflect a dynamic relationship between raw material properties, provenance, and hominin mobility. Exotic raw materials are generally more resistant to edge attrition compared with those available locally, which may have incentivized their transport over long distances and more extensive reduction. Cores produced on raw materials from distant sources also exhibit more complex core reduction strategies than locally acquired materials. While this pattern is partially due to the differences in the quality of knappable stone, bifacial centripetal and multifacial core reduction strategies also arise due to the continuous transport and use of exotic raw materials. Moreover, the variation in stone tool reduction is not consistent with neutral models of stone tool transport and discard. These results demonstrate that ecological factors such as raw material provenance and physical properties have strong impacts on reduction intensity and the technological strategies used by hominins.